Peace Education in Afghanistan: A Comparative Study of Conflict and Post-Conflict School Textbooks - Yazdani, Hafiza (In Factis Pax: Journal of Peace Education and Social Justice, 2020)
Afghanistan has experienced numerous educational curricula supporting its different governments’ policies regarding the establishment of formal education. Afghanistan’s school textbooks were published in support of alternate ideological regimes or governments during the years 1979 to 2002. From 2003 to 2014, the Afghanistan Islamic Republic government, with support from international donor agencies, worked to change the direction of education towards peace, free from political intervention and favouritism. The purpose of this research is to evaluate three different approaches to education in Afghanistan by examining a range of school textbooks, from three distinct political and cultural regimes, from a peace education perspective. It focuses in particular on the extent to which the objectives of peace education appear in Afghanistan’s newly developed school textbooks between the years 2004 and 2014. School textbooks from the Communist People’s Democratic Party of Afghanistan (PDPA), the Islamic State of Afghanistan (ISAG), and the current Afghanistan Islamic Republic Government (AIRG) were analysed using directive qualitative content analysis. Using components of the Standish analytical framework utilised in the Peace Education Curricular Analysis Project (2016), three objectives of peace education are surveyed in the Afghanistan data: 1. recognizing violence, 2. resolving conflict non-violently, and 3. fostering an environment of positive peace.